Physical and Chemical Processes and the Morphofunctional Characteristics of Human Erythrocytes in Hyperglycaemia - Revin, Victor V.; Klenova, Natalia A.; Gromova, Natalia V.; Grunyushkin, Igor P.; Solomadin, Ilia N.; Tychkov, Alexander Y.; Pestryakova, Anastasia A.; Sadykhova, Anna V.; Revina, Elvira S.; Prosnikova, Ksenia V.; Bourdon, Jean-Christophe; Zhelev, Nikolai (Frontiers in Physiology, 2017)
Background: This study examines the effect of graduated hyperglycaemia on the state and oxygen-binding ability of haemoglobin, the correlation of phospholipid fractions and their metabolites in the membrane, the activity of proteolytic enzymes and the morphofunctional state of erythrocytes. Methods: Conformational changes in the molecule of haemoglobin were determined by Raman spectroscopy. The structure of the erythrocytes was analysed using laser interference microscopy (LIM). To determine the activity of NADN-methemoglobinreductase, we used the P.G. Board method. The degree of glycosylation of the erythrocyte membranes was determined using a method previously described by Felkoren, B.I. et al. Lipid extraction was performed using the Bligh and Dyer method. Detection of the phospholipids was performed using V. E. Vaskovsky method. Results: Conditions of hyperglycaemia are characterised by a low affinity of haemoglobin to oxygen, which is manifested as a parallel decrease in the content of haemoglobin oxyform and the growth of deoxyform, methemoglobin and membrane-bound haemoglobin. The degree of glycosylation of membrane proteins and haemoglobin is high. For example, in the case of hyperglycaemia, erythrocytic membranes reduce the content of all phospholipid fractions with a simultaneous increase in lysoforms, free fatty acids and the diacylglycerol (DAG). Step wise hyperglycaemia in incubation medium and human erythrocytes results in an increased content of peptide components and general trypsin-like activity in the cytosol, with a simultaneous decreased activity of µ-calpain and caspase 3. Conclusions: Metabolic disorders and damage of cell membranes during hyperglycaemia cause an increase in the population of echinocytes and spherocytes. The resulting disorders are accompanied with a high probability of intravascular haemolysis.